2020
DOI: 10.1016/j.cmet.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Hour Time-Restricted Eating Reduces Weight, Blood Pressure, and Atherogenic Lipids in Patients with Metabolic Syndrome

Abstract: Highlights d 10 h time-restricted eating (TRE) in metabolic syndrome (MetS) promotes weight loss d TRE in MetS reduces waist circumference, percent body fat, and visceral fat d TRE in MetS lowers blood pressure, atherogenic lipids, and glycated hemoglobin d Benefits of TRE are ''add-ons'' to statin and anti-hypertensive medications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
702
6
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 592 publications
(858 citation statements)
references
References 42 publications
42
702
6
28
Order By: Relevance
“…The health benefits of intermittent fasting on aging, antioxidant stress, metabolism and cardiovascular disease have been demonstrated in human and animal studies [18,[24][25][26][27], but its effect on gut microbiota remains largely unclear. In our study, we found 30 days of daily fasting (16 h fasting) led to significantly increased level of Akkermansia and deceased level of Alistipes.…”
Section: Discussionmentioning
confidence: 99%
“…The health benefits of intermittent fasting on aging, antioxidant stress, metabolism and cardiovascular disease have been demonstrated in human and animal studies [18,[24][25][26][27], but its effect on gut microbiota remains largely unclear. In our study, we found 30 days of daily fasting (16 h fasting) led to significantly increased level of Akkermansia and deceased level of Alistipes.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, TRF lowers blood cholesterol and sugar levels, reduces body weight, inflammation and dysbiosis, while increasing energy expenditure, motor control and endurance (Chaix et al, 2019b). Human studies confirmed TRE's potential as a healthpromoting intervention and showed that TRF can help improve a number of metabolic markers including weight, body fat, blood pressure, energy intake and endurance, in particular in individuals at risk for metabolic syndrome (Chaix et al, 2019b;Wilkinson et al, 2020). TRF is distinct from DR as its health benefits do not require a reduction in caloric intake.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, dietary strategies that focus on the timing of eating and duration of fasting (i.e., chrono-nutrition), rather than the type, quality or quantity of foods, have been demonstrated to improve metabolic health independent of weight loss [12,13]. Specifically, time-restricted feeding (TRF, in which daily food intake is restricted to between 8-10 h) is a dietary strategy that has emerged as a practical intervention for weight loss, and improving insulin resistance along with other markers of whole-body health [10,[12][13][14][15][16]. Controlled (i.e., meals provided) 'early' TRF (eTRF; 0800-1500 h) improved both beta cell function in men with prediabetes [13] and 24-h glucose area under the curve (AUC) in individuals with obesity [12].…”
Section: Introductionmentioning
confidence: 99%